IMMUNE MECHANISMS OF DETOXIFICATION ACTION OF MINERAL WATER IN RATS AT CONDITIONS OF CHRONIC EMOTIONAL STRESS - Bakholdina, E.I. (World of Medicine and Biology, 2014)
In experimental studies performed on 70 white rats, a 5-minute series of experiments showed that the course application mineralized CF in rats with chronic emotional stress is largely restores the detoxification function of the immune system and prevents the development of symptoms of EI. Some features of the mechanism of this effect. The data obtained can serve as a justification for the creation of prevention aimed pathogenesis of chronic emotional stress with the use of natural factors.
Keywords: chronic emotional stress; endogenous intoxication; mineral water